Violência, gênero, punição: as estratégias discursivas dos operadores da Lei Maria da Penha na construção da verdade - Dantas, Gina Oliveira (2013)
This research analyzes the discursive strategies of the operators of the Maria da Penha Law on the true construction of the criminal cases of domestic violence against women. Problematizes therefore the resources produced by the defense and prosecution to succeed in its arguments, and the decision to acquit or convict the defendant in accordance with the intuitive power associated with the duty of the judge. With an ethnographic approach of instruction in Juvenile Court hearings of Women in Fortaleza observe the ritual interaction among participants with dramaticidades performances and site-specific. With the reading of sentences is possible to analyze more theses defended by the prosecution and the defense as well, recording the speeches are articulated as victims and defendants in construction of truth. Through interviews and observation perceives the involvement of gender in judging cases in legal disputes as well as the difficulty of law professionals in defining what is meant by gender for the enforcement of the law, taking effect in speech legal. Moreover, other results of the research showed recognition of urgent protective measures as the asset of Maria da Penha Law, the difficulties when making the event crimination accusatory, the social construction of crime of violence against women and the existence of senses justice between different law operators and users of the law.